PREFERENSI KONSUMEN DALAM MEMBELI RUMAH TIPE MENENGAH DI KABUPATEN BANTUL (Studi Pada Perumahan di Kecamatan Banguntapan dan Kasihan) - , Deny Kurniadi S, Dra. Wahyu Hidayati, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The growth of housing in the districts of Banguntapan and Kasihan, Bantul Regency has increased significantly in the past view years because of the several beneficial factors. To meet consumer demand for housing in the districts of Banguntapan and Kasihan, developers should be able to formulate marketing strategies based on consumerâs needs. The important factor in marketing is the prediction of consumerâs preferences in attributes of housing. Delivering a better combination of attributes in a product will help developer in home sales. This research is conducted to analyze which attribute is important for residential preferences. Attributes which used on this research is location, security, housing size, payment options, and facility. The personal characteristics studied were gender, age, educational level, child, and family income. Data used in this research is the primary data based on questionnaire to consumer who purchasing house in Banguntapan dan Kasihan. The analysis tools which are used in this research are conjoint analysis and logit analysis. Conjoint analysis by using SPSS is used to get the most important and unimportant attribute. Logit analysis by using eviews intend to identify the significant factor of personal characteristic to residential preferences. By the conjoint analysis, this research found that the important attribute of residential preferences are security, location, and facility. However, the unimportant attribute of residential preferences is housing size and payment options. In logit analysis, the most important personal characteristic which influence costumer is the educational level. Another variable of personal characteristics which has made impact are gender, age, and family income. However, personal characteristic which has no impact for consumerâs preferences is the child factor.